Improvement of routing protocol in wireless sensor network for energy consumption to maximize network lifetime - A. Othman, Emad (2013)
Wireless Sensor Networks (WSNs) consist of thousands of tiny nodes having the capability of sensing, computing, and wireless communications. Many routing, power management, and data dissemination protocols have been specifically designed for WSNs where energy consumption is an essential design issues. Due to energy constraints, the deployment and maintenance of WSNs should be easy and scalable to maintain the network lifetime. A comprehensive energy efficient hierarchical cluster-based routing protocol was proposed for continuous stream queries in wireless sensor network. The routing scheme and algorithm has the common objective of trying to extend the lifetime of the sensor network. We introduce cluster head-set idea for cluster-based routing where several clusters are formed with the deployed sensors to collect information from target field. On rotation basis, a head-set member receives data from the neighbour nodes and transmits the aggregated results to the distance base station. For a given number of data collecting sensor nodes, the number of control and management nodes can be systematically adjusted to reduce energy consumption quite significantly and prolongs the life time of sensor network. This document is a study about hierarchical cluster-based routing protocol algorithm where the implementation was done using Matlab simulator to study the performance of this algorithm in term of lifetime. We show that existing energy models over-estimate life expectancy of a sensor node by 30–58% and also yield an “optimised” number of clusters which is too large. Simulation results show that our hierarchical clustering protocol balances the energy consumption well among all sensor nodes and achieves an obvious improvement on the network lifetime.